The effect of ethnography-based outdoor learning methods on elementary students’ activities and learning outcomes - Hendratno, Hendratno; Wiryanto, Wiryanto; Istiq'faroh, Nurul; Primaniarta, M. Gita (Institute of Advanced Engineering and Science, 2024)
The cultural approach as a social studies learning resource can be carried out using ethnography-based outdoor learning methods for elementary school students. It adopts a quantitative research methodology employing experimental techniques. The population used is class V (fifth-grade) students in a sub-district. The number of students identified was 172. The sampling technique used was purposive sampling. Purposive sampling was utilized to select participants, dividing them into experimental and control groups. The quasi-experimental approach employed a posttest-only design with a nonequivalent group procedure. Hypothesis testing was selected to further examine the relationship between the independent and dependent variables. Multivariate analysis of variance (MANOVA), was employed to analyze questionnaire responses and learning results, yielding a significant value of 0.000, which is less than 0.005, thus accepting the alternative hypothesis (Ha). The findings indicate statistically significant influence of ethnography-based outdoor learning activities for both students’ engagement and academic performance in fifth-grade classrooms. These results underscore the potential of integrating indigenous knowledge-based learning innovations into elementary education.